Anxiety in patients with permanent cardiac pacemaker aged > 60 years old - Vasileiou, Stella; Iordani, Moschoula Mina; Martinis, Illias; Nikitopoulou, Alexandra; Sakiqi, Jona; Sekeroglou, Eleni; Tsampoula, Ilianna; Dousis, Evangelos (Health & Research Journal, 2020)
Introduction: A cardiac pacemaker is a small implanted device to control abnormal heart rhythms. According to estimates, 3 million individuals worldwide live with an implanted permanent pacemaker (PPM) while about 600 thousand pacemakers are implanted, annually. Purpose: to explore anxiety of pacemaker recipients as well as all the associated demographic and self-reported characteristics. Material and Method: 100 outpatients with PPM were enrolled in the study. Collection of data was performed by the completion of the “Self-rating Anxiety Scale Zung (SAS)” which included patients’ characteristics. Results: From the 100 participants 65% were men, 66% were >70 years old, 60% married, 50,5% of primary education and 90% lived in Attica. In terms of anxiety, 50% of recipients scored less than 48 on SAS scale (wide of range: 20-80) indicating mild to low levels of anxiety. Regarding associated factors, anxiety was found to be statistically significantly associated with gender (p=<0,001), understanding of provided information (p=<0,001), understanding of precautions in electromagnetic fields (p=0,021), desire for more frequent and long term follow-up and devise assessment (p=<0,001 and p=<0,001, respectively). Conclusions: Though pacemaker is an opportunity to prolong survival, however systematic assessment of anxiety and all the associated factors is considered to be of primary importance in clinical pacemaker settings.